Introducing The Creation of A Free Website Paud Unit in Pasarwajo Subdistrict - Saleh, Rachman; Adnan, Adnan; Marwah, Marwah; Inayah, Nur (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
The general purpose of this activity is to assist the PAUD unit to find out how to make website which is a medium of information dissemination and communication between paud units and related parties. With the PAUD unit website, there are several benefits, including being present in providing positive content for the public to realize a healthy internet, encouraging paud units to present positive and creative paud unit activity information, child guardians and the public can know various things about PAUD units directly, and foster public confidence in paud units. Kec.Pasarwajo there are many PAUD units both public and private. Implementation of assistance in 14 kindergartens of Pasarwajo Subdistrict. The problem does not yet have a PAUD unit website. So it is considered necessary to carry out assistance to paud units, especially in pasarwajo subdistrict. The activity begins with exposure to free website creation through wordpress and continues with direct practice assistance. The results of the activity showed that paud units in pasarwajo district of buton regency with participants of PAUD unit operators totaling 14 PAUD units in pasarwajo districts had been able to create a free website through wordpress. In addition, assistance has an impact on the spirit of operators in pasarwajo sub-district.